2020
DOI: 10.1002/jppr.1634
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of mental health training for community pharmacy staff members and consumers

Abstract: Background: Community pharmacy staff in rural and remote areas need to have the skills to recognise mental health signs and symptoms, provide support and appropriate advice. Aims: To evaluate the impact of Mental Health First Aid (MHFA) training through collaborative sessions attended by pharmacy staff and community members. Methods: Pharmacy staff, alongside members of the local farming community, attended collaborative MHFA training in four Queensland towns. This study evaluated the training through pre-and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 12 publications
(14 reference statements)
0
9
0
Order By: Relevance
“…One targeted community pharmacists, pharmacy assistants (ie, those who dispense under the supervision of a pharmacist), and members of four local farming communities in Queensland, Australia. 32 The second targeted lay people, pharmacists, general practitioners, and patients, including survivors of suicide attempt in Germany, Hungary, Portugal, and Ireland 33 (Table 1). Two of the five student pharmacist suicide prevention gatekeeper programs were embedded in Mental Health First Aid (MHFA) training programs (40%), but the content and assessments were different.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One targeted community pharmacists, pharmacy assistants (ie, those who dispense under the supervision of a pharmacist), and members of four local farming communities in Queensland, Australia. 32 The second targeted lay people, pharmacists, general practitioners, and patients, including survivors of suicide attempt in Germany, Hungary, Portugal, and Ireland 33 (Table 1). Two of the five student pharmacist suicide prevention gatekeeper programs were embedded in Mental Health First Aid (MHFA) training programs (40%), but the content and assessments were different.…”
Section: Resultsmentioning
confidence: 99%
“…31 Two of the six studies provided written case scenarios in which participants gave written feedback based on a hypothetical patient with suicidal warning signs (33%). 28,32 All five trainings for student pharmacists contained a role play or interactive component. Three (60%) contained background information and statistics on suicide [27][28][29] and two addressed medication counseling (40%) one addressed risk of medication use in a suicide attempt 28 and the other provided a scenario of a medication related ethical dilemma and review of medication history.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They reported that developing and maintaining good relationships with patients was one of the most important factors for its successful implementation. Shams and Hattingh [ 14 ] evaluated the impact of the MHFA training across four towns in Australia. Community pharmacists reported having a better understanding of mental health issues, recognising the signs and symptoms earlier and felt more confident engaging in mental health conversations [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Shams and Hattingh [ 14 ] evaluated the impact of the MHFA training across four towns in Australia. Community pharmacists reported having a better understanding of mental health issues, recognising the signs and symptoms earlier and felt more confident engaging in mental health conversations [ 14 ]. This highlights the potential for community pharmacies to play an important role in providing mental health support.…”
Section: Introductionmentioning
confidence: 99%